A Field Experiment on the Effects of Ethnicity and Socioeconomic Status on the Quality of Representation. Issue 3 (23rd January 2019) - Habel, Philip; Birch, Sarah
Abstract : The principle of equal representation is the cornerstone of modern democracy, yet there have been concerns that the benefits of representation can be skewed, advantaging some over others. We argue that elected officials will be more responsive to constituents whom they perceive as more like themselves and more likely to be politically active. We examine inequalities in representation in a parliamentary democracy where, intrinsic to the institutional framework, there is a long‐standing reputation for serving constituent needs: the United Kingdom. We also advance the literature by focusing on the expediency of responsiveness and the helpfulness of response. Drawing on a field experiment, we find both an overall high level of responsiveness and helpfulness but also biases affecting MP's responsiveness. Our findings raise important questions about equal access to representation, even in a political system where constituency service is the norm and expectation.